A Meta-Analysis of Microbial Therapy Against Metabolic Syndrome: Evidence From Randomized Controlled Trials - Pan, Binhui; Liu, Xiujie; Shi, Jiangmin; Chen, Yaoxuan; Xu, Zhihua; Shi, Dibang; Ruan, Gaoyi; Wang, Fangyan; Huang, Yingpeng; Xu, Changlong (Frontiers in Nutrition, 2021)
Background and aims: Metabolic syndrome (MetS) causes a great public health burden to human society, accompanied with the significant intestinal dysbiosis. Here we carried out a meta-analysis to qualify randomized controlled trials (RCTs) and systematically evaluate the effect of microbial therapy on MetS. Methods and results: Forty-two RCTs were eligible for this meta-analysis after searching the PubMed, Cochrane and Embase. Pooled estimates demonstrated that treatment with microbial therapy significantly reduced waist circumference (WC) (SMD = -0.26, 95% CI -0.49, -0.03), fasting blood glucose(FBG) (SMD = -0.35, 95% CI -0.52, -0.18), total cholesterol (TC) (SMD = -0.36, 95% CI -0.55, -0.17), low-density lipoprotein cholesterol (LDL-C) (SMD = -0.42, 95% CI -0.61, -0.22) and triacylglycerol (TG)(SMD = -0.38, 95% CI -0.55, -0.20), but increased high-density lipoprotein cholesterol (HDL-C) (SMD = 0.28, 95% CI 0.03, 0.52). Sensitivity analysis indicated that after eliminating one study utilizing Bifidobacteriumlactis, results became statistically significant in diastolic blood pressure (DBP) (SMD = -0.24, 95% CI -0.41, -0.07), Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) (SMD = -0.28, 95% CI -0.54, -0.03), while body mass index (BMI) showed significant difference after eliminating one study utilizing oat bran (SMD = -0.16, 95% CI -0.31, -0.01). There was still no significant effect in systolic blood pressure (SBP), hemoglobin A1c (HbA1c%). Conclusion: In MetS patients, conditioning with microbial therapy notably improves FBG, TC, TG, HDL-C, LDL-C, WC, BMI (except for the study using oat bran) and HOMA-IR, DBP (except for the study using Bifidobacteriumlactis), however, with no effect in SBP, HbA1c%.